Sun Protection Counseling by Pediatricians has Little Effect on Parent and Child Sun Protection Behavior - Cohen, Liza (2012)
OBJECTIVE: To compare counseling concerning sun protection and outdoor exercise with the parent’s report of the behavior of a child age 9 to 16 years old. STUDY DESIGN: Structured interviews of medical personnel in three Chicago area practices elicited information about counseling methods and recommendations. In each practice, a convenience sample of parents completed a self-reported survey of their and their child’s behavior. RESULTS: Sun protection counseling occurred more frequently than exercise counseling in all practices (p=0.014). Sun protection counseling was associated with parental prompting (p =0.004), performing a summer camp physical (p=0.002), and the child having a sunburn (p=0.003). After controlling for the child’s age, sex, and skin tone, sun protection counseling was not associated with the child’s use of sun protection. In multivariate analysis of the child’s sun protection behavior, parental sunburns, indoor tanning in the last 12 months, perception of skin cancer risk and sun protection self-efficacy were significant. (p=.02) Children who pursued outdoor sports were twice as likely to use inadequate sun protection and sustain sunburns. (CI 1.3–1.7) CONCLUSIONS: The child’s sun protection behavior was influenced by parental sun protection, parental perception of skin cancer risk and parental sun protection self-efficacy; therefore, sun protection for children needs to be aimed at parents as well as children. Communication with parents in a way that incorporates the principles of motivational interviewing may be more effective in promoting behavioral change than admonitions to use sunscreen.